2007
DOI: 10.1152/japplphysiol.00008.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immune function in sport and exercise

Abstract: Regular moderate exercise is associated with a reduced incidence of infection compared with a completely sedentary state. However, prolonged bouts of strenuous exercise cause a temporary depression of various aspects of immune function (e.g., neutrophil respiratory burst, lymphocyte proliferation, monocyte antigen presentation) that usually lasts approximately 3-24 h after exercise, depending on the intensity and duration of the exercise bout. Postexercise immune function dysfunction is most pronounced when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
665
4
82

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 794 publications
(776 citation statements)
references
References 45 publications
25
665
4
82
Order By: Relevance
“…Few data exist to support differences in resting immune function with training status [40]. Nieman et al reported elevated NK cell activity in elite rowers compared with controls [41].…”
Section: Discussionmentioning
confidence: 99%
“…Few data exist to support differences in resting immune function with training status [40]. Nieman et al reported elevated NK cell activity in elite rowers compared with controls [41].…”
Section: Discussionmentioning
confidence: 99%
“…Antagonicamente, o exercício pode levar a um quadro imunossupressor, com aumentos nos episódios de ITRS, caso executado intensamente e/ou por períodos prolongados que extrapolem as limitações físicas dos atletas ou quando o período de recuperação é insuficiente [1][2][3][4][5][6][7][8][9][10][11][12][13] .…”
Section: Introductionunclassified
“…Os aumentos nos episódios de ITRS tem relação com: aumentos nas contagens dos neutrófilos e diminuição nos linfócitos circulantes 1,14 ; redução da proliferação dos linfócitos e na citotoxicidade das células Natural Killers (NK) 1,13,14 ; aumento da apoptose dos linfócitos 1,13 ; redução da imunidade da mucosa, em decorrência de diminuições nas concentrações séricas de anticorpos específicos, principalmente a imunoglobulina (Ig)-A 1,3,7,15 e aumentos nas concentrações séricas das citocinas pró-inflamatórias, principalmente interleucina (IL)-1β, IL-6 e fator de necrose tumoral (TNF)-α. Essas modificações são mais evidentes após provas de maratona 1,7,9 e testes prolongados em esteira 1,14 .…”
Section: Introductionunclassified
“…Exercise can profoundly influence health [1], and there is mounting evidence that the mechanism of these beneficial effects is related, in part, to the impact of exercise on immune function [2]. Precisely how the various physiological perturbations that accompany physical activity (ranging from acidosis to heat to the secretion of potent endocrine hormones and neuroadrenergic mediators) actually alter immune function is still not well understood.…”
Section: Introductionmentioning
confidence: 99%